Financial Management for Business Sustainability Creating Used Goods Creations in Kembangan Selatan District, West Jakarta - BADAWI, Ahmad; MURTININGSIH, Dewi; NUGROHO, Lucky; HIDAYAH, Nurul (Indonesia Strategic Sustainability, 2024)
Financial management is the planning, management, storage and control of funds or assets owned by a business. Understanding financial literacy and how to manage finances is very important and must be a priority because it will have an impact on business sustainability. Limited financial management knowledge can result in a lack of planning and impact on welfare. On the other hand, if financial management is carried out well, it can be said that the person is responsible for the funds they own. Every business actor must have knowledge and skills in managing finances for sustainability. A business run by GoodGood for now. This won't happen. Community service activities will be carried out in the South Kembangan District area and will be attended by residents of Kembangan District. Activities are planned with good development programs in the fields of Human Resources, Marketing and Finance. The activities carried out are related to the description of business management starting from side funding, product creation and product sales to marketing strategies. The aim of this PKM activity is not only to understand the importance of utilizing the materials used, but also to create business opportunities with creativity and innovation carried out by business actors. PKM activities will end with a discussion and question and answer session as well as filling out a questionnaire. The output of PKM activities will be published in mass media, modules or journal publications.